Development of a new and environmentally-friendly method to evaluate phenolic compounds from Flos Lonicerae Japonicae with ultra-high performance supercritical fluid chromatography (UHPSFC) combined with chemometrics. Issue 35 (23rd August 2018) - Jiang, Hai; Yang, Liu; Xing, Xudong; Yan, Meiling; Yang, Bingyou; Yang, Lin; Cui, Mingyu; Wang, Qiuhong; Kuang, Haixue
Abstract : The chemical variation of 10 batches of Flos Lonicerae Japonicae from different geographical origins was investigated by quantitation of phenolic acids.. Abstract : In recent years, ultra-high performance supercritical fluid chromatography (UHPSFC) has become a superior technique and powerful analysis tool for the efficient separation of natural products. The chemical variation of 10 batches of Flos Lonicerae Japonicae (FLJ) from different geographical origins was subsequently investigated by quantitating seven phenolic acids. The effect of different columns, temperature, outlet pressure, and flow rates on the separation of seven phenolic acids was studied. Four chromatographic parameters were optimized using central composite design (CCD) tests, and a fusion index established using the Derringer function was used to evaluate the results. An ACQUITY UPC 2 BEH (100 × 3.0 mm, 1.7 μm) column was selected as the optimal column for the untargeted method. From the CCD tests, the optimal values for temperature and outlet pressure were determined to be 45 °C and 2900 psi, respectively. Our findings confirm that UHPSFC-PDA combined with chemometrics could be used as an efficient method for quality control of herbal medicine.